Self-Efficacy as a Predictor of Interdialytic Weight Gain (IDWG) in End Stage Renal Disease Patients - Noviantika Sari; Sri Mugianti; Naya Ernawati; Supono Supono (JURNAL INFO KESEHATAN, 2025)
Excessive interdialytic weight gain in End Stage Renal Disease (ESRD) patients may reduce their quality of life well-being. High self-efficacy (belief in one's own ability) can increase the patient's readiness to live a better quality of life. The purpose of this study is to ascertain how interdialytic weight gain (IDWG) and self-efficacy relate to each other in patients with end-stage renal disease. This study uses a correlational quantitative design type with a cross-sectional method approach. The sampling method used purposive sampling with a total of 107 respondents. Univariate data analysis test to determine the characteristics of respondents. The Spearman Rank correlation test is used in bivariate analysis to determine the relationship between two variables, while the cross sectional design is to analyze the relationship between variables that have been collected at one time simultaneously. The results of this study were 69 patients (64.5%) had low self-efficacy and a moderate IDWG category of 56 patients (52.3%). The Rank-Spearman test results obtained a p-value of 0.000 and a positive Spearman correlation value (r) of 0.565. The conclusion that can be drawn is that there is a strong and significant relationship between self-efficacy and IDWG in patients with end stage renal disease. The suggestion from this study is that hospital managers consider making policies related to the service and care of ESRD patients by providing regular education related to fluid restriction compliance by applying media in the form of educational videos or leaflets or posters in the waiting room.